Impulse control and related disorders in Parkinson’s disease - Vargas, Antonio Pedro; Cardoso, Francisco Eduardo Costa (Arquivos de Neuro-Psiquiatria, 2018)
Neuropsychiatric disorders are common among patients with Parkinson’s disease and may appear in any stage of the disease. However, these disorders often go undiagnosed and receive insufficient treatment. Observations in recent years have revealed that dopamine replacement therapy may lead to the development or worsening of conditions, such as gambling disorder, compulsive sexual behavior, compulsive buying and binge eating, in addition to punding and dopamine dysregulation syndrome. The pathophysiology of these disorders seems to be related to abnormal dopaminergic stimulation of the basal regions of the basal ganglia, especially via nigro-mesolimbic pathways. The aim of the present study was to perform a literature review on impulsivity, impulse control disorders and related conditions among patients with Parkinson’s disease, with emphasis on their epidemiology, clinical characteristics and treatment.
Keywords: Parkinson’s disease; disruptive, impulse control, and conduct disorders; levodopa; dopamine agonists; impulsive behavior; bulimia